A Navigation and Reservation Based Smart Parking Platform Using Genetic Optimization for Smart Cities - Aydin, Ilhan; Karakose, Mehmet; Karakose, Ebru (Ieee, 2017)
With the development of technology, smart devices are becoming more common in everyday life. The development of devices that can connect to the Internet and transmit data has been a source of inspiration for smart city designs. The common problem in our cities is the difficulty of finding free parking slots. The parking problem causes traffic to congest and people who go to work are looking for a place. In this study, a navigation and reservation based parking proposal system was developed for smart cities. The proposed method involves the development of small devices that send data to the internet using the internet of things (IoT) technology. The free parking space closest to the current location is found by genetic algorithm. The proposed method is tested for different scenarios and accurate results are obtained.
5th International Istanbul Smart Grid and Cities Congress and Fair (ICSG) -- APR 19-21, 2017 -- Istanbul, TURKEY
Keywords: Multi-objective optimization; parking navigation; reservation-based parking; smart city; smart parking